2016
DOI: 10.1371/journal.pone.0163464
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 Is the Strongest Predictor of Whole-Body Insulin Sensitivity in Psoriatic Arthritis

Abstract: ObjectivesTo evaluate the correlation between inflammatory measures and whole-body insulin sensitivity in psoriatic arthritis (PsA) patients.MethodsFor the present study, 40 nondiabetic PsA patients were recruited. A standard oral glucose tolerance test (OGTT) was performed. The insulin sensitivity index (ISI), insulinogenic index (IGI) and oral disposition index (ODI) were calculated from dynamic values of glucose and insulin obtained during OGTT.ResultsIn our study population, mean ISI was 3.5 ± 2.5, median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
2
22
0
2
Order By: Relevance
“…Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features. Further, these data integrate our previous studies in which complement C3 was identified as the strongest predictor of insulin resistance in RA and PsA patients [26][27][28], despite in this study, we have not found any significant correlation between the presence of NAFLD and increased insulin resistance, thus supporting the hypothesis that complement C3 may reflect different mechanisms of metabolic derangement. In our cohort we found an overall prevalence of NAFLD in RA of 25%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features. Further, these data integrate our previous studies in which complement C3 was identified as the strongest predictor of insulin resistance in RA and PsA patients [26][27][28], despite in this study, we have not found any significant correlation between the presence of NAFLD and increased insulin resistance, thus supporting the hypothesis that complement C3 may reflect different mechanisms of metabolic derangement. In our cohort we found an overall prevalence of NAFLD in RA of 25%.…”
Section: Discussionsupporting
confidence: 90%
“…Complement system activation [22] has been shown in liver biopsies from patients with NAFLD compared to healthy controls [23]. Moreover, our group previously demonstrated a significant association between complement C3 and insulin resistance (IR) in psoriatic arthritis (PsA) [26,27] and RA patients [28][29][30]. Moreover, our group previously demonstrated a significant association between complement C3 and insulin resistance (IR) in psoriatic arthritis (PsA) [26,27] and RA patients [28][29][30].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, we feel the need to clarify that the main aim of our manuscript was not that of confirming a direct, unimpeachable, unidirectional causal correlation between complement C3 and the future development of NAFLD, but rather to provide a hypothesis-generating basis for further, adequately powered longitudinal studies aiming at investigating in details the processes linking complement system to metabolic disturbances in RA patients, as already suggested by other studies published by our group. [2][3][4] ORCID Francesco Ursini…”
Section: Response To the Letter To The Editor By Shadmani Et Almentioning
confidence: 99%
“…We truly appreciated the precious and highly qualified contribution-given the leading expertise of the authors in the field of biostatistics and epidemiology-and largely agree with them that the crosssectional design of our study may significantly limit the ability of our results to support definitive conclusions regarding the direction of the relationship between C3 and NAFLD.However, we feel the need to clarify that the main aim of our manuscript was not that of confirming a direct, unimpeachable, unidirectional causal correlation between complement C3 and the future development of NAFLD, but rather to provide a hypothesis-generating basis for further, adequately powered longitudinal studies aiming at investigating in details the processes linking complement system to metabolic disturbances in RA patients, as already suggested by other studies published by our group. [2][3][4] ORCID Francesco Ursini…”
mentioning
confidence: 99%